Active vehicle: a new approach integrating AmI technology for trust management in VANET. (2018) - Ltifi, Amel; Zouinkhi, Ahmed; Bouhlel, Med Salim
Ambient intelligence (AmI) is a new concept that interests many researchers in different domains that require highly innovative services, such as vehicular ad hoc networks (VANETs). In fact, concerning vehicle trust management, the majority of the proposed solutions are dependent on road equipments and the investigation into a scalable infrastructure in all the roads is unreasonable. Therefore, road security should be managed by vehicles themselves. Hence, we have introduced the concept of 'active vehicle' that combines the power of AmI and the V2V technologies. In this paper, we propose a new secured communication model between active vehicles for alert spreading. Through this new model, traffic accident alerts are verified depending on the trust level of the sender. A trust management system has the responsibility to cut out the spread of false warnings through the network.